Changes between Version 13 and Version 14 of u/johannjc/scratchpad7
- Timestamp:
- 10/12/15 16:06:21 (9 years ago)
Legend:
- Unmodified
- Added
- Removed
- Modified
-
u/johannjc/scratchpad7
v13 v14 53 53 $A_\parallel = \frac{\kappa_\parallel}{\rho c_v \left ( \lambda_\parallel + 1\right ) }$ and $A_\perp = \frac{\kappa_\perp}{\rho c_v \left (\lambda_\perp + 1 \right )}$ 54 54 55 and $B_{\parallel, ij} = b_i b_j$ and $B_{\perp, ij} = n^2 B^{-2} b_i b_j \left ( 1 - \delta_{ij}\right )$55 and $B_{\parallel, ij} = b_i b_j$ and $B_{\perp, ij} = n^2 B^{-2} \left ( \delta_{ij}-b_i b_j \right )$ 56 56 57 57 Now to solve this implicitly, we need to replace $T$ with $T_*$ where